Dunia Dalam Cengkeraman Invisible Hand (Telaah Kritis Atas Globalisasi Melalui Mega Proyek Merauke Integrated Food and Energy Estate) - Nyoman Ayu Sukma Pramestisari (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2020)
The Mega Agenda of the Merauke Integrated Food and Energy Estate (MIFEE) project in Papua is one of the global efforts to respond the 2008 world food crisis. This project includes the procurement of food and energy barns for world needs. Around one million hectares of land were cleared for extractive industries in the form of corn, palm oil, rice and sugar cane in the hope of absorbing the local workforce. Unfortunately, this industrialization process has implications for the loss of forests as a source of life, drought, the environment polluted by extractive industrial waste, exploitation of workers also horizontal conflicts. Through the Empire and Multitude approach by Negri and Hardt the analysis leads to the occurrence of biased interests of local, national and global elites as empire in the MIFEE project. With the main principle of neoliberalism, namely the accumulation of capital, the empire exploits natural and human resources on the pretext of global interests. Seeing the struggles of the people are often accommodated by politicalÂ devide et impera, the offer of multitude can be an alternative solution. Communities all over the world can help in their own ways in the simplest lines, such as reducing consumptive actions and saving lives.Â